The Impact of Childhood Maltreatment: A Review of Neurobiological and Genetic Factors - McCrory, Eamon; De Brito, Stephane A.; Viding, Essi (Frontiers in Psychiatry, 2011)
Childhood maltreatment represents a significant risk factor for psychopathology. Recent research has begun to examine both the functional and structural neurobiological correlates of adverse care-giving experiences, including maltreatment, and how these might impact on a child's psychological and emotional development. The relationship between such experiences and risk for psychopathology has been shown to vary as a function of genetic factors. In this review we begin by providing a brief overview of neuroendocrine findings, which indicate an association between maltreatment and atypical development of the hypothalamic-pituitary-adrenal axis stress response, which may predispose to psychiatric vulnerability in adulthood. We then selectively review the magnetic resonance imaging (MRI) studies that have investigated possible structural and functional brain differences in children and adults who have experienced childhood maltreatment. Differences in the corpus callosum identified by structural MRI have now been reliably reported in children who have experienced abuse, while differences in the hippocampus have been reported in adults with childhood histories of maltreatment. In addition, there is preliminary evidence from functional MRI studies of adults who have experienced childhood maltreatment of amygdala hyperactivity and atypical activation of frontal regions. These functional differences can be partly understood in the context of the information biases observed in event-related potential and behavioural studies of physically abused children. Finally we consider research that has indicated that the effect of environmental adversity may be moderated by genotype, reviewing pertinent studies pointing to gene by environment (GxE) interactions. We conclude by exploring the extent to which the growing evidence base in relation to neurobiological and genetic research may be relevant to clinical practice and intervention.